The use of quality tools to reduce surface defects of painted steel structures - Knop, Krzysztof (Manufacturing Technology Journal, 2022)
The article presents the results of the use of quality instruments - tools and techniques - in order to reduce surface defects of steel structures on the example of a selected element - engine cover of asphalt milling machines. The article shows the potential of using selected quality tools - basic and new - in the service of quality analysis and improvement. Quantitative analyzes were presented out using the Pareto-Lorenz diagram and the c control chart, qualitative analyzes using the Ishikawa diagram and the FMEA method, quantitative & qualitative analyzes using the interrelationship diagram and matrix diagram, and it was proposed quality improvement using qualitative tools such as affinity diagram, and PDPC diagram. The most common defects of painted surfaces turned out to be improper thickness and surface contamination. As it has been shown, the experience of employees is largely responsible for the cause of these defects, which was also confirmed by other analyses carried out with the use of quality tools. The training was the most frequent method of prevention. It has also been shown that special attention should be paid to quality control, its effectiveness, and quantity. The article proves that correctly used quality tools can contribute to the improvement of the quality of manufactured products, helps in solving various quality problems.
Keywords: defects of painted surfaces; steel structures; quality tools; improvement